Effects of laser energy density on morphology features and microstructures of the single molten track in selective laser melting - Wang, Sen; Wang, Linzhi; Liu, Jiquan; Yang, Runqi; Li, Jing; Wang, Guoyu (Frontiers in Materials, 2023)
Single molten track (SMT) is the basic unit of the selective laser melting (SLM) process, of which the morphology features and microstructures have great significance on the molding quality. In this study, the effects of laser energy density (LED) on characteristics of SMT were studied with 316 L stainless steel processing by SLM. The results indicate that an optimized range of LED was between 200 and 500 J/mm3, which was the best for SLM process of 316 L leading to beautiful SMT appearance such as continuous uniform water-ridge-like surface, good contour straightness, smooth edges, little adhesive powder, and high densification. The microstructures of the SMT molten pool are mainly composed of equiaxed cellular and columnar dendrites. As the LED decreased, the cellular became smaller and disappeared, while the length and width of columnar crystals even gradually increased. The size of the cellular varies between 0.43 and 1.70 μm with the LEDs increase. The relationship between SMT characteristics and LED found in this work can be readily used to optimize SMT and control the microstructures in situ, and the laser energy density range that the work has identified will simplify most of the guess work in additive manufacturing.